Clinical Reasoning: A 37-Year-Old Man With Involuntary Movements, Gait Disturbance, and Hyperesthesia. (17th May 2022) - Meng, Dylan; Alsalem, Aseel; Zhang, Christina; Chen, Tychicus
Abstract : A 37-year-old right-handed Indigenous Canadian man presented with 2.5 years of progressive involuntary movements, gait instability, and hyperesthesia. He complained of constant, involuntary head and trunk movements, severe speech disturbance, dysphagia, blurred vision, and binocular diplopia in all directions. He took no regular medications and drank no alcohol. Medical history was noncontributory. Family history was notable for a great uncle who died in his fifties from an unspecified gait disorder.